Analisis Pengelompokan Desa Berdasarkan Indikator Sosial Ekonomi Menggunakan Metode K-Means - Sigit Nugraha; Fauriatun Helmiah; Abdul Karim Syahputra (Jurnal Algoritma, 2026)
This study aims to cluster villages in Rahuning Subdistrict, Asahan Regency, based on socioeconomic indicators to support targeted development planning. The data used covers ten villages with four main criteria that have been normalized into numerical values. The method used is K-Means Clustering with three clusters (K=3). The analysis process includes determining the initial centroids, calculating distances using Euclidean Distance, and iterating until convergence is achieved. The results of the study show the formation of three groups: the high cluster, consisting of Rahuning Village, Rahuning III Village, Perbaungan Village, and Aek Songsongan Village; the medium cluster, consisting of Rahuning I Village, Batu Anam Village, Gunung Melayu Village, and Sei Piring Village; and the low cluster, consisting of Rahuning II Village and Air Batu Village. An evaluation using the Silhouette Score method yielded a value of 0.57, indicating that the quality of the clustering falls into the “fairly good” category with relatively clear separation between clusters. This study contributes a data-driven approach to identifying socioeconomic disparities among village areas, thereby serving as a foundation for local governments to formulate more effective, targeted, and equitable development policies.